Manajemen pemasaran pendidikan meningkatkan minat masyarakat di SDIT Permata Bunda Bandar Lampung - Apriyadi, Masruron (STIES ALIFA, 2021)
Marketing management plays a very important role in every institution because many institutions are competing to provide education to children in the country. The marketing management of the Integrated Islamic Elementary School (IIES) of Permata Bunda Bandar Lampung helps increase the interest of prospective new students. This study uses a descriptive method with a qualitative approach. Methods of collecting data through interviews, observation and documentation. The subjects of this study were principals, waka curriculum, teachers, and school staff. Data analysis is done by reducing and displaying the data as well as the final description/validation. As a result, it was found that the education and marketing management of IIES Permata Bunda Bandar Lampung was divided into the following three phases. 1) Planning was carried out earlier this year at a meeting between the principal and stakeholders. The plan includes forming a marketing committee (PPDB), setting marketing objectives, determining marketing media, and recruiting students. 2) Marketing implementation is carried out by distributing pamphlets, installing banners and marketing through the teacher council's Whatsapp story, posting Instagram pamphlets and uploading school profile videos to YouTube accounts. 3) Supervision is carried out by controlling the implementation of marketing so that school management is carried out as planned so that the objectives will be realized. This supervision will be carried out at the end of the implementation of school marketing management as material for future assessments. The school's efforts to generate public interest through a marketing mix strategy are: a) product offerings, b) pricing/costs, c) displaying the location of IIES Permata Bunda Bandar Lampung, d) promotions, e) increasing human resources, f) displaying pictures of facilities and infrastructure for IIES Permata Bunda Bandar Lampung. G.) perform the procedure.